mRNA and miRNA Transcriptome Profiling of Granulosa and Theca Layers From Geese Ovarian Follicles Reveals the Crucial Pathways and Interaction Networks for Regulation of Follicle Selection - Li, Qin; Hu, Shenqiang; Wang, Yushi; Deng, Yan; Yang, Shuang; Hu, Jiwei; Li, Liang; Wang, Jiwen (Frontiers in Genetics, 2019)
Follicle development is characterized by the recruitment, growth, selection, and dominance of follicles, and follicle selection determines the lifetime reproductive performance. However, in birds, the molecular mechanisms underlying follicle selection still remain elusive. This study analyzed genome-wide changes in the mRNA and miRNA expression profiles in both the granulosa and theca layers of geese ovarian follicles before selection (4-6 mm and 8-10 mm follicles) and after selection (F5). The sequencing results showed that a higher number of both differentially expressed (DE) mRNAs and DE miRNAs were identified between 8-10 mm and F5 follicles compared to those between the 4-6 mm and 8-10 mm follicles, especially in the granulosa layer. Moreover, a short time-series expression miner analysis identified a large number of DE mRNAs and DE miRNAs that are associated with follicle selection. Functional enrichment analysis showed that DE genes in the granulosa layer during follicle selection were mainly enriched in five pathways related to junctional adhesion and two pathways associated with lipid metabolism. Additionally, an interaction network was constructed to visualize interactions among protein-coding genes, which identified 53 junctional adhesion- and 15 lipid regulation-related protein-coding genes. Then, a co-expression network between mRNAs and miRNAs in relation to junctional adhesion was also visualized, and mainly included acy-miR-2954, acy-miR-218, acy-miR-2970, acy-miR-100, acy-miR-1329, acy-miR-199, acy-miR-425, acy-miR-181, and acy-miR-147. Furthermore, miRNA-mRNA interaction pairs related to lipid regulation were constructed including acy-miR-107, acy-miR-138, acy-miR-130, acy-miR-128, and acy-miR-101 during follicular selection. In summary, these data highlight the key roles of junctional adhesion and lipid metabolism during follicular selection and contribute to a better understanding of the mechanisms underlying follicle selection in birds.